Factors Affecting MSMEs in Using QRIS and Electronic Data Capture (EDC) as a Cashless Payment Method: Evidence from Sorong City, Southwest Papua - Hidayah, Nurul; Ridwan, Akmal; Prihandoko, Nugroho Dwi; Nurhani, Nurhani (International Journal of Business Studies, 2023)
Rapid progress has been made in the development of cashless payment systems. As can be seen from the positive level of public acceptance of this payment method development standard, moreover this trend has become necessary for rural communities. QRIS and debit card payment via EDC are the non-cash methods that MSMEs players in Sorong city utilize the most frequently. Sorong city is quite developed province of Southwest Papua Indonesia, which is well regarded as a commercial and industrial hub. According to reports as of January 2022, the use of QRIS by merchants in the Sorong city itself has not met the target set by Bank Indonesia. This research aims to examine the variables that affect MSMEs players decision to use QRIS and EDC for cashless transactions. In this quantitative research, the variables predictor used are the extended Technology Acceptance Model (TAM) by Davis, with are perceived risk as X1, perceived ease of use as X2, and perceived usefulness as X3. Convenience sampling was the sampling technique utilized, with questionnaires distributed to the 60 MSMEs players throughout Sorong city. Multiple linear regression analysis is used to determine the significance relationship between predictor variables and response variable. The findings demonstrate that there is significant relationship between perceived ease of use and perceived usefulness on the decision of MSMEs players to use QRIS and EDC for cashless payments in their businesses, while the usage decision not significantly affected by the variable of perceived risk. The research's empirical evidences are expected to increase local business literacy and provide a reference for the government and policymakers who make rules about cashless payment systems.